Modulation of TNF-a, TNF-a receptors and IL-6 after treatment with AM3 in professional cyclists - Córdova, A.; Sureda, A.; Pons, A.; Alvarez-Mon, M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Changes in IL-6, TNF-a, and TNF-a receptors - sTNFRI and sTNFRII - were evaluated in a group of professional cyclists treated with immunomodulator AM3 (Inmunoferón®) for 6 months of training and competition.